Tetramethylpyrazine promotes stroke recovery by inducing the restoration of neurovascular unit and transformation of A1/A2 reactive astrocytes - Feng, Xue-feng; Li, Ming-cong; Lin, Zi-yue; Li, Man-zhong; Lu, Yun; Zhuang, Yu-ming; Lei, Jian-feng; Wang, Lei; Zhao, Hui (Frontiers in Cellular Neuroscience, 2023)
2,3,5,6-Tetramethylpyrazine (TMP) as an active ingredient extracted from a traditional Chinese herbal medicine Ligusticum chuanxiong Hort. has been proved to penetrate blood-brain barrier (BBB) and show neuroprotective effects on cerebral ischemia. However, whether TMP could regulate astrocytic reactivity to facilitate neurovascular restoration in the subacute ischemic stroke needs to be urgently verified. In this research, permanent occlusion of the middle cerebral artery (MCAO) model was conducted and TMP (10, 20, 40 mg/kg) was intraperitoneally administrated to rats once daily for two weeks. Neurological function was evaluated by motor deficit score (MDS). Magnetic resonance imaging (MRI) was implemented to analyze tissue injury and cerebral blood flow (CBF). Magnetic resonance angiography (MRA) was applied to exhibit vascular signals. Transmission electron microscopy (TEM) was performed to detect the neurovascular unit (NVU) ultrastructure. Haematoxylin and eosin (HE) staining was utilized to evaluate cerebral histopathological lesion. The neurogenesis, angiogenesis, A1/A2 reactivity, aquaporin 4 (AQP4) and connexin 43 (Cx43) of astrocytes were observe with immunofluorescent staining. Then FGF2/PI3K/AKT signals were measured by western blot. Findings revealed TMP ameliorated neurological functional recovery, preserved NVU integrity, and enhanced endogenous neurogenesis and angiogenesis of rats with subacute ischemia. Shifting A1 to A2 reactivity, suppressing excessive AQP4 and Cx43 expression of astrocytes and activating FGF2/PI3K/AKT pathway might be potential mechanisms of promoting neurovascular restoration with TMP after ischemic stroke.